Yarn parameterization and fabrics prediction using image processing - Carvalho, Vítor (2013)
This paper presents the main characteristics and functionalities of a system based on image processing techniques applied to quality assessment of yarns. In Textile Industry we used image processing to determine yarn mass parameters as well as yarn production characteristics. A low cost solution based on a web-pc camera plus the optics of a low cost analogue microscope and a software tool based on IMAQ Vision from LabVIEW was designed. Several tests were performed and compared with other methodologies of yarn parameterization validating the proposed solution. With the results one can support that this can be an alternative solution to the traditional yarn testers, with several advantages (among others, low cost, weight, volume, easy maintenance and reduced hardware). Moreover, this yarn parameterization can be used to assess the quality of the fabrics resultant.